2021
DOI: 10.3390/ijerph18041956
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Intentions to Commit Dating Violence among Taiwanese University Students: Application of the Extended Theory of Planned Behavior

Abstract: Dating violence (DV) constitutes a major public health and safety issue worldwide; however, only limited research into this important subject has been conducted in Taiwan. This study examined university students’ intention to commit DV, based on the expanded theory of planned behavior (TPB), with a history of family violence and gender stereotyping also included as further factors in the original TPB model. A total random sample consisting of 450 university students from four universities in four regions in Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Several authors have shown that stable individual factors influence the relative weights of the different predictors in the model (Ajzen, 2011). Therefore, some scholars have expanded the original theory to include, for instance, cultural factors and personal values (e.g., Lee et al, 2006;Lin et al, 2021). Based on meta-analyses of the use of the theory, these additions appear to be particularly important when examining behaviors with moral dimensions in which one must balance out personal rewards (cf.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Several authors have shown that stable individual factors influence the relative weights of the different predictors in the model (Ajzen, 2011). Therefore, some scholars have expanded the original theory to include, for instance, cultural factors and personal values (e.g., Lee et al, 2006;Lin et al, 2021). Based on meta-analyses of the use of the theory, these additions appear to be particularly important when examining behaviors with moral dimensions in which one must balance out personal rewards (cf.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Combining individual as well as sociocultural factors to explain behavior, this theory has already commonly been used to explain SDV (Miller et al, 2010), also among youth. For instance, a study among university students in Taiwan found that multiple TBP concepts, including positive attitudes towards dating violence, positive perceived injunctive norms regarding SDV, and higher perceived behavioral control to perform violence against dating partners were all related to dating violence perpetration (Lin et al, 2021a). Moreover, a study on Chinese adolescents found that for boys, higher perceived behavioral control and more positive social norms towards rejecting peers' SDV were related to more behavioral intentions to reject peers' SDV (Li et al, 2010).…”
Section: Understanding Sdv Through the Theory Of Planned Behaviormentioning
confidence: 99%
“…17,18 In addition to the direct application of TPB, several studies have shown that TPB has been extended in different areas with success. [19][20][21][22][23] To some extent, subjective norms in the TPB are virtually a kind of social norm. 24,25 Social norms shape people's motivation and behavior based on the social environment.…”
Section: Introductionmentioning
confidence: 99%